Carbon dioxide capture using functionalized multi-wall carbon nanotubes by EDA - Hassan, Ibrahim F.; Majeed, Najwa S.; Al-salman, Ahmed Amer (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Carbon dioxide (CO2) is the primary factor considered to be responsible for global warming. CO2 capture technology has been considered an important issue to decrease greenhouse gas emissions. The current research investigates the functionalization of Multi-Wall Carbon nanotubes (MWCNTs) by Ethylenediamine (EDA) solution which is used for CO2 capture at various operating conditions. Surface functionality groups and morphology of MWCNTs and physical properties were analyzed by X-ray diffraction (XRD), Fourier Transforms Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), surface area Brunauer Emmett and Teller (BET). The physical and chemical properties of CNTs have changed after the functionalization process, which enhances MWCNTs adsorption for CO2 gas. According to the study’s results, during the functionalization process, amine groups bound to carbonaceous surfaces created CO2 adsorption sites on multi-walled CNTs, increasing the adsorption capacity of MWCNTs. The CO2 adsorption capacity was determined by volumetric technique at temperatures from 309 to 333 °K and a pressure of 1 to 7 bar. The exothermic nature of the adsorption process was indicated by the decreasing of CO2 adsorption capabilities via MWCNTs and MWCNTs-EDA with temperature rising. The results showed that the MWCNTs-EDA are a potential low-temperature adsorbent for CO2 capture. In addition, 0.6968 mmol g−1 of CO2 was adsorbed by MWCNT-EDA at 309 °K, while raw MWCNT adsorbed only 0.3428 mmol g−1 at the same condition. Both the Freundlich and Langmuir adsorption isotherms were used to model the experimental data, with the conclusion being that the Freundlich model fits the data well.